Problems of prescribing nonsteroidal anti-inflammatory drugs for reproductive-aged women with ankylosing spondylitis - O. A. Krichevskaya; T. V. Dubinina; A. E. Karateev (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the first-line medications for ankylosing spondylitis (AS); their action is associated with blockade of the enzyme cyclooxygenase 2 and with a mediated decrease in the synthesis of prostaglandins (PGs). However, PGs play an important role in regulating the functions of the female reproductive system. The paper presents an update on the participation of PG in folliculogenesis, ovulation, implantation, and development of the embryo, and labor activity. Based on experimental and clinical findings, the authors discuss whether due to inhibition of the synthesis of PGs, NSAIDs are able to cause ovulation failure, including luteinized unovulated follicle syndrome and spontaneous abortions. Further investigation is justified to determine the most optimal NSAID therapy regimens when planning pregnancy and during gestation in women with AS.